Hubungan Antara kepemimpinan Dengan Iklim Organisasi dan kepuasan kerja di Fakultas Kedokteran Universitas Gadjah Mada - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK The objective of this research was to study the relationship between leadership and organizational climate as well as job satisfaction at the Faculty of Medicine, Gadjah Mada University, Yogyakarta. It was expected that the result of this research will elicit some information that can be used to plan succesfully priority changes needed to reach goals of the organization This research was viewed from individual behaviour. The hypothesis was: there is a strong correlation between leadership and organizational climate as well as job satisfaction The subjects studied were staff members who were asked to complete the Michigan's Institute for Social Research questionnaire. The Product Moment Correlation (Part Whole Correlation) between leadership and organizational climate was significant (r = 0,6364